Responsible management in Africa. volume 1, - Ogunyemi, Kemi; Ogunyemi, Omowumi; Anozie, Amaka (Emerald Publishing Limited, 2022)
Africa is one of the world's oldest economies, yet little is known about the wisdom that traditionally guided responsible management, with most work in the field employing Western perspectives. Responsible Management in Africa brings African voices to complement existing knowledge and practice by presenting indigenous values and practices that promote responsible business. From the Zunde Rambo philosophy in managing organisations in Zimbabwe and judicious business applications of Ubuntu and Batho Pele principles in South Africa, to lessons from an intergenerational business in Yorubaland, Nigeria; from Akan management styles and gold trade in ancient Ghana to the impact of acculturation on management in Morocco and Tunisia and the system that fortified responsible business in Uganda, and more, this volume brings African worldviews to the fore of humanism and ethics in management. The chapters present academic perspectives and hands-on applications of approaches to managing responsibly, especially regarding integrating ethical practices into business and assuring sustainability through ethical profitability. Responsible Management in Africa delivers a rich reservoir of indigenous value-narratives based on a well-balanced philosophical anthropology, with the aims of enriching global knowledge, in the philosophy of management and in business ethics, and of contributing much-needed insights for leaders around the world to manage enterprise responsibly, be it public or private sector.